KRITIK SOSIAL DALAM CERITA KYAI AGENG GRIBIG SEBAGAI UPAYA PENANAMAN NILAI BUDAYA GENERASI MUDA - Mustaqim, Mustika Nurul; Kurwidaria, Favorita (Universitas Sebelas Maret, 2025)
Folklore contains social criticism that can be used as an effort to instill cultural values in the younger generation. The younger generation today is largely unfamiliar with folklore, especially folklore in their surrounding areas, whereas in these folklores there are noble values that can be used as guidelines for behavior. This study aims to describe the social criticism contained in the story of Kyai Ageng Gribig. This study is a qualitative study with data in the form of words or sentences containing social criticism and data sources in the form of informants and documents regarding the story of Kyai Ageng Gribig. This study uses a sampling technique in the form of purposive sampling. Data collection techniques are carried out by interviews and document analysis. The data analysis technique uses interactive analysis techniques according to Miles and Huberman in the form of data collection stages, data reduction, data presentation, and drawing conclusions. Based on the results of the story analysis, nine social criticisms were found according to Soekanto's theory. Social criticism was found based on social problems of poverty, crime, family disorganization, problems of the younger generation towards modern society, war, violations of norms in society, population problems, environmental problems, and bureaucracy. These results can be used as lessons for readers to act well in life.